Development of the Agrarian Sector of the Ukrainian Economy: Forecasts and Prospects - Kolesnikov, S.; Mishura, V. (Економічний вісник Донбасу, 2019)
In the article the modern problems of development of agrarian sector of economy of Ukraine in the conditions of institutional changes are revealed. The development of the agrarian sphere of the country in the context of institutional changes is analyzed. Prospects for the development of the agricultural sector of the national economy have been determined, taking into account the existing risks and possible options for public policy. The correlation analysis of farms and non-farms for the period from 2012 to 2018 is conducted. Thus, the dependence of Y on X was studied. In the specification step, a pairwise linear regression was chosen. It estimated its least squares parameters. The statistical significance of the equation is verified using the Fisher coefficient and determination. Only 10.35% of the total variability of Y is found to be explained by the change in X. The statistical significance of the model is due to the small sample size and the influence of other factors on the effective factor U. It is proved that to ensure a rational level of compliance of agricultural producers with agro-technological requirements it is necessary to take a set of measures, in particular: to introduce a favorable regime of import of imported mineral fertilizers and means; introduce economic incentives for land owners, land users and land tenants to increase soil fertility and improve their economic condition.